Molecular phylogeny and morphology reveal a new species of Amauroderma (Basidiomycota) from China - Song, Jie; Xing, Jia-Hui; Decock, Cony; He, Xiao-Lan; Cui, Bao-Kai (Phytotaxa, 2016)
The phylogeny of Amauroderma and related genera were studied using DNA sequences from the internal transcribed spacer (ITS) and 28S nuclear ribosomal RNA gene regions. Amauroderma concentricum sp. nov. is described. The species is characterized by the yellowish brown to reddish brown pileal surface with concentric zones, a white pore surface unchanged when bruised, single to multiple stipes, small pores (4–5 per mm), and subglobose to globose and double-walled basidiospores, 8–9.2 × 7.2–8 µm. The phylogenetic analysis presented here confirmed that Amauroderma as traditionally accepted is not monophyletic.